Entwicklungstendenzen der Steinbuttfischerei in der Ostsee - Frieß, Claus-Christian (1999)
The economical value of turbot (Psetta maxima) from the Baltic Sea has distinctly increased in the past decade. Compared to the eighties the catches of this species on the main fishing grounds increased threefold. Besides a more directed fishery on this species and an improved catch statistic the main reason for this fact is probably an increased stock size. Improved protection measures caused three consecutive strong year-classes. The main parameters of the turbot stock are presented.